A binary integer programming model for university course timetabling problem and a case study - Kocken, Hale Gonce; Ozdemir, Rumeysa; Ahlatcioglu, Mehmet (ISTANBUL UNIV, 2014)
In this study, we have presented a novel binary integer model for University Course Timetabling Problem (UCTP). Besides the model is structured as the general format, model's aim is to make a desirable timetable for a department of a domestic university which has been doing its own course timetabling, manually. Similarly to the literature, constraints are divided into two categories: hard and soft. Hard constraints include the constraints such as uniqueness, completeness, consecutiveness, laboratory, pre-assignment, type of variable and some of the daily-course load and session constraints. And the soft ones include the non-conflict constraints which prevent conflict of sequential student groups' course times, the daily-load constraint which provides that a student group should take at least two courses in a school day, and the session constraints which provide a day off between sessions of a two-sectioned course. The objective function of the model, which is aimed to be maximized, should provide the high quality of education enhanced by all of the assignments and the fulfilling demands and expectations of the related department/faculty member. The model is implemented within the data of previous semester of the related Department.
Keywords: Timetabling; Education Timetabling; Course Timetabling; University Course Timetabling Problem; Binary Integer Programming; Business & Economics